KESIAPAN PRASARANA DAN SARANA PROTEKSI KEBAKARAN PADA PASAR ASOKA (SENGGOL KRENENG) BERDASARKAN PERMEN PU NO: 20/PRT/M/2009 - Parthami Lestari, Ayu Putu Utari (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Fire accidents are events that can occur anytime and anywhere. Quoted from the website page of Denpasar BPBD, fires were the most disasters that occurred in the city of Denpasar with 96 cases in 2016, although this number decreased from 2015 which amounted to 137 incidents. In the Minister of Public Works Regulation Number 20 / PRT / M / 2009 concerning the Technical Guidelines for Management of Urban Fire Protection, it has been determined that the safety of the community inside the building and its environment must be a primary consideration especially for fire hazards so that people can carry out their activities and improve productivity and quality of life. The discussion of this paper is limited only to the Environmental Fire Protection Infrastructure and Facilities which consist of: Water supply, Environmental Roads, Communication Facilities, Data on environmental fire protection systems located within the main control room in a separate and easily accessible building, Social / Public Facilitation which is allocated for building fire posts with a minimum land area of ​​900 m2 and a minimum building area of ​​400 m2, Light Fire Extinguishers (APAR), Car pumps, Car ladders as needed, and other supporting equipment. As one of the biggest markets in Denpasar City, Pasar Kreneng should properly get attention in the readiness of infrastructure and facilities in the face of fire hazards. This study will discuss the availability of facilities and infrastructure in Senggol Kreneng Market in the face of fire disasters according to Permen PU No. 20 / PRT / M / 2009. At the end of the study it can be concluded that Denpasar Kreneng Market has facilities and infrastructure that still need to be enriched to face future fires, especially in terms of construction of social facilities and public facilities in the form of fire posts, etc. Keywords: fire, Asoka market, Permen PU 20/2009